Lipase immobilised on silica monoliths as continuous-flow microreactors for triglyceride transesterification - Alotaibi, Mohammed; Manayil, Jinesh C.; Greenway, Gillian M.; Haswell, Stephen J.; Kelly, Stephen M.; Lee, Adam F.; Wilson, Karen; Kyriakou, Georgios (Reaction Chemistry & Engineering, 2018)
Lipase immobilised on silica monoliths has been prepared and applied as biocatalytic continuous-flow microreactors for the transesterification of tributyrin as a model bio-oil component. Candida antarctica lipase was trapped within the pores of silica monoliths, and its successful immobilisation was demonstrated by the hydrolysis of 4-nitrophenyl butyrate to 4-nitrophenol. Lipase immobilised on silica monoliths was active for the transesterification of tributyrin at ambient temperature, with reactivity as a function of the methanol : tributyrin ratio, flow rate, temperature, and textural properties. Monoliths with a high surface area and large meso- and macropore channels enhanced the transesterification activity through improved molecule diffusion. The optimum immobilised lipase microreactor exhibited almost quantitative ester production for >100 h at 30 °C without deactivation